Evaluation of renal effects of dapagliflozin in diabetic rats with subacute exposure - ERCAN, FERİHA (My University, 2023)
Dapagliflozin (DAPA), a sodium glucose co-transporter 2 (SGLT2) inhibitor, is used for the treatment of type 2 diabetes. Although several studies have demon-strated its protective effects on the kidney, the FDA warns about the risk of DA-PA-induced nephrotoxicity. SGLT2 inhibitors may induce oxidative stress and inflammation in the kidney due to their mechanism of action. In the present study, it was aimed to clarify the molecular effects of DAPA on the kidney. Diabetes was induced by single injection of streptozotocin (STZ) (35 mg/kg b.w.) after the rats were fed with high-fat diet for two-weeks. Diabetic rats were administered with DAPA at 10 mg/kg by oral gavage for 28 days. The oxidative stress, inflammation and apoptosis induction potentials of DAPA were evaluated. The morpholog-ical changes and apoptosis were investigated by histological examinations. The findings showed that DAPA treatment reduced oxidative parameters and slightly inhibited inflammatory mediator levels. According to the histological examinations, DAPA ameliorated the diabetes-induced changes and apoptosis. As a result, DAPA showed a protective effect on the kidney by alleviating oxidative stress and inhibiting inflammation and apoptosis. However, further studies are needed to determine the long-term effects of DAPA on the kidney in diabetic patients.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; General Pharmacology, Toxicology and Pharmaceutics; Dapagliflozin; diabetes; nephrotoxicity; renoprotective effect; SGLT2 inhibitors; Dapagliflozin; SGLT2 inhibitors; nephrotoxicity; diabetes; renoprotective effect